Innovating traditional building materials in Chembe, Malawi: assessing post-consumer waste glass and burnt clay bricks for performance and circularity. Issue 4 (4th July 2021) - Mahdjoub, Noredine; Kalina, Marc; Augustine, Alex; Tilley, Elizabeth
ABSTRACT: Across the Global South, post-consumer waste glass is an often dumped, and under-utilised resource. Even in Malawi, with widespread return schemes, many barriers exist, inhibiting reuse, and necessitating appropriate solutions. The purpose of this article is to evaluate the performance of post-consumer waste glass as a coarse aggregate within burnt clay bricks, and to assess the feasibility for the recovery of this waste material from dumped stocks within Chembe. Using a brick design and testing methodology, which could be replicated within a rural African context, we tested a range of glass additions (both quantity and size of particle) for compressive strength and water absorption properties. Our results suggest that waste glass can function as a performance enhancer, with positive effects on compressive strength observed at up to 10% crushed waste glass content. These findings support existing literature on glass waste additions, yet show that optimal results can also be had with post-consumer waste glass and in low income, and less technology-reliant contexts. Moreover, our findings suggest that current above-ground stocks of waste glass are sufficient to support the production of hybrid building materials for decades, however further innovation is necessary in order to achieve a sustainable mode of practice.